La desviación en la poesía de Leopoldo María Panero - Śmiłek, Ewa (Romanica Silesiana)
Leopoldo María Panero is a modern Spanish poet and a member of the Novísimos group. Critics have often labeled him insane, transgressive and cursed. His mental illness, schizophrenia, makes him one of the most controversial Spanish poets and grants him a unique vision of reality. Culture and society generate and develop rules, limits and prohibitions which every member of a given society is obligated to obey. In Panero’s writing morality is likened to a constraint which the poet transgresses. This article concentrates on one of the most important issues in Panero’s writing, namely, transgressive sexuality (with its socially unacceptable forms, such as incest or necrophilia). What is more, by using the most significant ideas of Georges Bataille, Sigmund Freud or Antoni Kępiński, this paper ponders on whether madness is enough to Key words: Leopoldo María Panero, modern Spanish poetry, sexuality, schizophrenia, transgression.